Abuso de posição dominante no Mercosul e na União Européia: uma análise da concorrência e seus efeitos - Furtado, Rogério Dourado (2011)
Competition law was created in the United States due to the need to curb cartels and abuse of concentration of economic and market power. Since then, other countries have also incorporated the antitrust law in their jurisdictions, with the aim of ensuring a more just and lawful competition, thus shaping our times. It was no different in Brazil, beginning in the 1930s to the present day with Law number 8.884/94, the so called Brazilian antitrust law. This bill marks the beginning of the Brazilian system for protection of the competition, which although much criticized, attempts to exercise its role of ensuring a competitive benefit to society. In this dissertation we discourse about what is dominant position and its abuse in the legislational context, both internal and external. We proceed with an analysis of the competition in Mercosur and the European Union economic blocks. Finally we compare both economic blocks since their beginnings, going through their integrational role until supranationality. We analyze the problems encountered and possible solutions to a satisfactory Mercosur Common market, along the lines of the European Union